Advanced Imaging Techniques in Preoperative Planning for Brain Tumor Resection: Evaluating the Impact on Surgical Precision and Neurological Outcomes - Gutiérrez Hernández, Fredy Agustín; Arias Audor, Giovanni Andres; Quintero Serrano, Natalia; Gutiérrez Robayo , Andrés Felipe; Gracia Guillén, Juan Sebastián; Torres García, Natalia Fernanda (Arandu UTIC, 2024)
This study investigates advanced imaging techniques and their impact on surgical precision and neurological outcomes in preoperative planning for brain tumor resections. Selected studies include large human sample sizes, peer-reviewed research, systematic reviews, and meta-analyses focusing on advanced imaging techniques and their impact on surgical precision and neurological outcomes. Latest imaging modalities experiments on animal studies are considered. Systematic review of recent literature on advanced imaging modalities—such as MRI, fMRI, PET, and DTI—and their application in preoperative planning. Our findings suggest advanced imaging techniques, including Functional MRI, Ultra-High Field MRI, Diffusion Tensor Imaging (DTI), PET/CT and Deuterium Magnetic Resonance Spectroscopy (2H MRS) improve surgical precision and neurological outcomes in brain tumor resections by enhancing tumor targeting, reducing morbidity, and improving resection accuracy. Future advancements should focus on integrating and optimizing these technologies to further improve preoperative planning and patient-specific treatment strategies.